2015
DOI: 10.1074/jbc.m115.650176
|View full text |Cite
|
Sign up to set email alerts
|

The Helicase Activity of Ribonuclease R Is Essential for Efficient Nuclease Activity

Abstract: Background: Escherichia coli RNase R contains an intrinsic RNA helicase activity. Results: Walker A and Walker B motifs located in the C-and N-terminal regions, respectively, are required for helicase activity. Conclusion: RNase R helicase activity utilizes the nuclease catalytic channel and stimulates the nuclease activity. Significance: These findings help to explain how RNase R efficiently degrades structured RNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 27 publications
5
38
0
Order By: Relevance
“…Recent singlemolecule FRET data indicate that both RNase R and its homolog, the Rrp44 subunit of the eukaryotic exosome (22,23), advance 3′-to-5′ along dsRNA in steps of approximately four base pairs through internal elastic coupling of their binding and catalytic sites (24). RNase R mutants that lack the nuclease activity required for processive motion nonetheless may separate hybridized strands of RNA (21,25), presumably through an entirely different, distributive mechanism similar to that described for DEAD-box helicases under certain conditions (26). Although RNase R appears to have a minor preference for adenine (13), no significant sequence-dependent behavior has been reported for this enzyme.…”
mentioning
confidence: 99%
“…Recent singlemolecule FRET data indicate that both RNase R and its homolog, the Rrp44 subunit of the eukaryotic exosome (22,23), advance 3′-to-5′ along dsRNA in steps of approximately four base pairs through internal elastic coupling of their binding and catalytic sites (24). RNase R mutants that lack the nuclease activity required for processive motion nonetheless may separate hybridized strands of RNA (21,25), presumably through an entirely different, distributive mechanism similar to that described for DEAD-box helicases under certain conditions (26). Although RNase R appears to have a minor preference for adenine (13), no significant sequence-dependent behavior has been reported for this enzyme.…”
mentioning
confidence: 99%
“…In the E. coli protein, we also identified Walker A and Walker B motifs that are responsible for ATP binding and consequent RNA helicase activity, and found that they are conserved in most mesophilic bacterial genera, but are absent from thermophilic bacteria (8), suggesting that the helicase is important for RNase R function. This conclusion was reinforced by biochemical analyses showing that the helicase activity is essential for efficient nuclease activity in vitro, particularly at lower temperatures, with duplexes containing short 3Ј overhangs, and with more stable RNA duplexes (8,9). Whether the helicase activity is also important for nuclease activity in vivo has been unclear.…”
mentioning
confidence: 99%
“…Escherichia coli RNase R contains an intrinsic RNA helicase activity (10), and recent work from our laboratory characterized this helicase and defined its relation to overall nuclease activity (8,9). In the E. coli protein, we also identified Walker A and Walker B motifs that are responsible for ATP binding and consequent RNA helicase activity, and found that they are conserved in most mesophilic bacterial genera, but are absent from thermophilic bacteria (8), suggesting that the helicase is important for RNase R function. This conclusion was reinforced by biochemical analyses showing that the helicase activity is essential for efficient nuclease activity in vitro, particularly at lower temperatures, with duplexes containing short 3Ј overhangs, and with more stable RNA duplexes (8,9).…”
mentioning
confidence: 99%
See 2 more Smart Citations